Marital quality in alcohol dependance syndrome: a comparative study between first time and repeatedly hospitalised patients - Jose, Kurian; Khess., Christoday R. J.; Uvais, N. A. (International Journal of Research in Medical Sciences, 2017)
Background: Marital quality is considered as a significant part of social well-being. Poor marital quality adversely affects physical and mental health as well as the overall quality of life. Moreover, it can significantly affect the course of alcohol dependance syndrome. The aim this study was to compare the marital quality among patients with alcohol dependance syndrome who are admit-ted for the first time and patients with alcohol dependance syndrome (ADS) who are admitted for multiple times. Methods: The sample consisted of each 30 patients with alcohol dependance syndrome who are admitted for the first time and patients with alcohol dependance syndrome who are admitted for multiple times, diagnosed as per international classification of diseases-10 diagnostic criteria for research. The sample population was evaluated using Severity of Alcohol Dependence Questionnaire and The Marital Quality Scale. The data was analysed using SPSS-16.0. Results: The severity of alcohol dependance was found to be significantly higher in the repeatedly hospitalised group when compared to first time admitted patients with ADS (p<0.01). The repeatedly hospitalised patients are found to be having significantly poor Marital Quality in the domains of Understanding, Rejection, Satisfaction, Affection, Despair, Decision Making, Dominance, Self-Disclosure, Trust and Role Functioning, when compared to first time admitted patients (p<.001). Conclusions: How problem use of alcohol affect marital quality is not settled in research till date, though most of the studies suggest a negative correlation. There are contradictory hypotheses regarding the effects of alcohol use on marital quality. Our study showed that patients with severe degrees alcoholism and who are admitted repeatedly have poor marital quality when compared to patients with lesser severity of alcoholism and admitted for the first time in Indian context.